Chronic Obstructive Lung Disease in young: Alpha 1 anti trypsin deficiency - Dhakal, S.S.; Agrawaal, K.K.; Bhatta, N.K. (Journal of Advances in Internal Medicine, 2015)
Alpha-1 antitrypsin (AAT) deficiency is a clinically under recognized inherited disorder. The main clinical manifestations relate to three separate organs: the lung, the liver, and the skin. In the lung, severe deficiency of AAT predisposes to chronic obstructive pulmonary disease. We present a case of 34 years male with a history of recurrent chest infections in past and treated in the line of bronchial asthma but not relieved. He was admitted on 22nd May 2011 at BPKIHS. He presented with type 2 respiratory failure and had features of severe pulmonary arterial hypertension and left lower lobe pneumonia. The patient got improved with the treatment and is doing well on follow up. The diagnosis should be strongly suspected in patients with history suggestive of bronchial asthma and with obstructive features. Journal of Advances in Internal Medicine 2014;3(2):65-67